PERHITUNGAN SATURASI MENGGUNAKAN DATA C/O LOG PADA SUMUR X DENGAN DAYA DORONG AIR - Pieter, Jimmy
Carbon and Oxygen Ratio (COR) on production well can be used for by-passed oil identification by calculate the fluid saturation. Reservoir Saturation Tool has been developed for C/O log measurement to make it possible to run on flowing condition so it does not affect well production process. Reservoir Saturation Tool has two detectors, each for near wellbore detection and formation detection. From the formation layers of X Well, intervals that suspected have by-passed oil are taken based on high COR and open hole log data. COR from those intervals analyzed by using combination of FCOR vs NCOR cross plotandFan Chart Method to get oil saturation. Result from this methodcan approach interpretation result from the service company although it tends to be inaccurate on formation with high shale contain.